MENINGKATKAN HASIL PRESTASI BELAJAR SISWA MELALUI KEGIATAN BIMBINGAN KELOMPOK DENGAN MODEL PARENTING - Widhia D.R., Nuri (Universitas Muria Kudus, 2017)
This research is classroom action research, conducted in class and outside class in the form of parenting group with research subject is the students of class IX D of SMP Negeri 1 Patikraja. This research is focused on group guidance activity with parenting model by supervisor teacher consistently and continuously in order to improve student's learning achievement. Research can be implemented with 3 cycles with the results of research indicates an increase in learning achievement outcomes from each stage of the cycle through try out results. The improvement of student achievement result can be seen with the average acquisition showing good improvement that is from try out I and II up 1.15% or from the average 54,85 to 62,93 then try out II to III from 62 , 93 to 63.91 or up 1.02%, then try out III to the district from 63.91 to 66.76 or up 1.04% and final national exam results from try out Regency 66.76 to 82.53 during national exam or up 1.24%.